Serum protein profile of Holstein cows during the transition period - Reis, J. F.; Madureira, K. M.; Silva, C. P. C.; Baldacim, V. P. A.; Fagliari, J. J. [UNESP]; Gomes, V. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2016)
The aim of this study was to evaluate longitudinally the serum protein profile of 13 Holstein cows during the transition period. Blood samples (n=78) were taken weekly, from the second week before parturition (M-2) to the third week after parturition (M3) for determination of serum protein profile by biochemical tests (total serum protein - PT) and SDS-PAGE electrophoresis, for the other proteins analyzed. PT values decreased gradually (P = 0.000) from M-2 (6.4g/dL) to M0 (6.2g/dL), increasing in subsequent moments (M3 = 7.3g/dL). The concentrations of the heavy chain (M-2=919.4; M-1=1074.5mg/dL) and the light chain of IgG (M-2=393.9; M-1=466.7mg/dL) were lower in pre-calving compared to post calving (M1=1,283.3; M2=1,374.2 and M3=1,630.3 mg/dL for the heavy chain, and M1=463.4; M2=573.7 and M3=651,8 mg/dL for the light chain of IgG). For IgA there was a decrease in the values (P=0.001), from M-2 (51.9mg/dL) to M1 (34.0mg/dL), and increase in M2 (45,4g/dL) and M3 (62,6g/dL). The values of haptoglobin (Hp) and ceruloplasmin (Cp) increased (P=0,000) from M-2 (Hp=16.6mg/dL; Cp=8.6 mg/dL) to M3 (Hp=60.9mg/dL; Cp=127.1mg/dl). Albumin showed slight variations during the transition period (P=0.000), while the serum transferrin (P=0.101) and acid glycoprotein (P=0.105) were stable. Body condition score (BCS) was also analyzed during the transition period, checking the difference (P=0.003) between M-2 (ECC=4.0) and M1 (ECC=3.0). It was also reported the occurrence of dystocia (4/13), retained placenta (1/13) and hypocalcemia (1/13) on the day of calving (M0) and uterine infections (5/13) and ketosis (1/13) occurring in the post calving. In conclusion, there was an increase in serum Hp and Cp, and a decrease in the immunoglobulins and transferrin amounts in Holstein cows during the transition period, related to diseases occurring during this period and the high BCS, promoting metabolic changes and immunosuppression.
Keywords: inflammation; proteins; peripartum; bovine